2009
DOI: 10.1186/1749-8546-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicines as a resource for liver fibrosis treatment

Abstract: Liver fibrosis is a condition of abnormal proliferation of connective tissue due to various types of chronic liver injury often caused by viral infection and chemicals. Effective therapies against liver fibrosis are still limited. In this review, we focus on research on Chinese medicines against liver fibrosis in three categories, namely pure compounds, composite formulae and combination treatment using single compounds with composite formulae or conventional medicines. Action mechanisms of the anti-fibrosis C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 98 publications
2
31
0
Order By: Relevance
“…We previously reported that cr had the strongest cytotoxicity among a selection of 16 anti-cancer chinese herbs in rat leukemia l-1210 cells, and a much higher inhibitory activity for growth of tumor cells was present in the water extract of cr, compared to extracts using other solvents (22). Our previous studies revealed that craE and its active compound, berberine, are promising anti-cancer drugs due to their low toxicity and liver protective properties (9)(10)(11)18,21). In the present study, we confirmed that regulation of certain specific miRNAs may also contribute to an anti-cancer effect (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that cr had the strongest cytotoxicity among a selection of 16 anti-cancer chinese herbs in rat leukemia l-1210 cells, and a much higher inhibitory activity for growth of tumor cells was present in the water extract of cr, compared to extracts using other solvents (22). Our previous studies revealed that craE and its active compound, berberine, are promising anti-cancer drugs due to their low toxicity and liver protective properties (9)(10)(11)18,21). In the present study, we confirmed that regulation of certain specific miRNAs may also contribute to an anti-cancer effect (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…medicinal plants have had an extensive history of use in cancer therapy, and plant-derived compounds have played an important role in the development of various clinically useful anti-cancer agents (18,19). Coptidis rhizoma (cr) is a species of goldthread native to china (Botanical dermatology database; http://bodd.cf.ac.uk) and one of the 50 fundamental herbs used in traditional chinese medicine (20).…”
Section: Discussionmentioning
confidence: 99%
“…One of the effective treatments in suppressing HCC is to control progress of chronic liver damage (Feng et al, 2009b). Recent years, herbal medicines as a resource for liver diseases have been attracted by the world wide scientists (Schuppan et al, 1999;Feng et al, 2009b;Seeff et al, 2001), among which Coptidis rhizoma (CR, Huanglian in Chinese) is one of the potential herbs (Feng et al, 2009b;Ye et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As of today, derivatives from plant remain as only suggestions and not proven treatments. The use of Coptidis Rhizoma may be suggested because of its similarity with bear bile in the traditional use according to Chinese Medicine theories, and both Coptidis Rhizoma and bear bile have similar clinical indications and scientific evidences in treating liver diseases [4-9]. However, there is no study reporting the comparative study on the anti-fibrotic action of Coptidis Rhizoma and bear bile and their underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of continuous and chronic liver injuries could induce liver fibrosis, among which Hepatitis B viral infection (HBV) is the main cause of liver fibrosis in China, while hepatitis C infection and alcoholic intoxication cause liver fibrosis in the United States, Europe and Japan [4]. Previous studies on the pathogenesis of liver fibrosis indicated that activation of hepatic stellate cells, over-expression and over-accumulation of extracellular matrix (ECM) protein, and collagen-like protein in liver tissue may be involved [10].…”
Section: Introductionmentioning
confidence: 99%